The effect of low viscous coir fiber resin composite immersion time on composition dissolution - Wijaya, Yongki Hadinata; Cevanti, Twi Agnita; Soesilo, Diana; Rochyani, Linda (Odonto : Dental Journal, 2023)
Background: E glass fiber dental is a fiber that is often used in dentistry. The availability of E glass fiber in Indonesia is still very limited. Various types of non-dental glass fiber materials are found in the market as engineering materials with relatively cheap prices so that they are expected to be used as an alternative to E glass fiber dental, which one of is coconut fiber. The composition of non-dental glass fiber is almost the same as that of dental E glass fiber. The composition affects the mechanical properties and chemical properties of the fiber. Glass fiber compositions such as Na2O and K2O will increase water resistance. Method: This study was conducted using a post test only control group design. The material used in this study was a composite of coconut coir fiber. The subjects of the coco fiber composite were divided into 4 groups for solubility test based on ISO 4049. The results obtained were analyzed using one-way ANOVA (p = 0.000). The results showed the lowest mean component solubility (%) was in the coconut fiber composite group A (0.476Â±0.03) and the highest yield was in the coco coir fiber composite D (0.6Â±0.01). Results: The results of the one-way ANOVA test showed a significant difference in the coco fiber composite in the solubility of the components (p